Cyntia żywa i Cyntia umarła. Literacka gra z odbiorcą w elegii 4.7 Propercjusza - Pypłacz, Joanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
In this article I analyse the theme of love and death as explored by Propertius in his Elegy 4.7. I also attempt to show that the problem of incongruence between this poem and the neighbouring Elegy 4.8 can be resolved by means of an aesthetically oriented reading of both poems.